가정전문간호사의 직접간호업무 스트레스와 직무만족도 - 김희승; 유소영; 김명자; 박재순; Kim, Hee-Seung; You, So-Young; Kim, Myung-Ja; Park, Chai-Soon (여성건강간호학회지, 2004)
Purpose: This study was aimed to investigate direct care stress and job satisfaction in home care nurses. Method: Subjects were 139 home care nurses of hospitals in urban cities. Data was collected by a self report questionnaire. Direct care stress was measured by Community Health Nurses Perceptions of Work-Related Stressors Questionnaire. Job satisfaction was measured by a visual analogue scale. Results: The average score of direct care stress was 60.4. There were significantly high direct care stress in those who had less than that 3 years experience than in their counterparts. The average score of job satisfaction was 79.5. There were significant high job satisfaction in those who willingly chose to work. Direct care stress negatively correlated with the length of office experience of the home care nurse. Conclusion: A direct care educational program should be developed for those who have less than 3 years experience to decrease their stress level.